Strengthening Ecotourism to Improve Quality of Life in Ubung Kaja Village through Creativity, Order, and Cultural Values - JAYAWARSA, A. A Ketut; SAPUTRA, Komang Adi Kurniawan; NARINDRA, Ngurah Mayun (Community Services: Sustainability Development, 2024)
This KKN-PPM (Student Community Service) program was conducted in Ubung Kaja Village, North Denpasar District, Denpasar City, from July 22 to August 24, 2024, with the theme "Strengthening Ecotourism to Improve the Quality of Life of the Community." This theme highlights efforts to build a sustainable tourism village through creativity in Ecobricks, English language proficiency, and concrete actions in environmental conservation. The theme integrates these three elements in a complementary way, positively impacting the community and the environment. Ecobricks, as a creative recycling product, can become a symbol of the environmentally-conscious tourism village. They can be used to create unique handicrafts with high commercial value while reducing plastic waste. Proficiency in English is crucial for promoting the tourism village to international tourists. Students, as the future ambassadors of the village, can create promotional materials, such as brochures or videos in English, to attract tourists. Environmental Cleanliness: Cleaning activities are a concrete effort to preserve nature and improve the community's quality of life. A clean environment makes the tourist village more attractive and comfortable for visitors. The overarching theme of this program is "sustainability." Activities such as creating eco-bricks, learning English, and cleaning the environment are concrete efforts to realize a sustainable tourism village. These activities provide not only economic benefits but also social and environmental advantages.